Enhancement of Cognitive Function by Andrographolide-Loaded Lactose β-Cyclodextrin Nanoparticles: Synthesis, Optimization, and Behavioural Assessment - Debashish Paramanick; Kagithala Naga Rani; Vijay Kumar Singh; Parakh Basist; Rahmuddin Khan; Jameel H. Al-Tamimi; Omar M. Noman; Mansour N. Ibrahim; Abdulsalam Alhalmi (MDPI AG, 2024)
This study investigates whether Andrographolide-loaded Lactose β-Cyclodextrin (ALN-βCD) nanoparticles enhance cognitive function, particularly spatial learning and memory. The successful conjugation of lactose to β-cyclodextrin was confirmed via 1H NMR spectroscopy, facilitating neuronal cell entry. The solvent evaporation method was used to create the nanoparticles, which were characterised for particle size, PDI, zeta potential, and drug release. The nanoparticles exhibited a size of 247.9 ± 3.2 nm, a PDI of 0.5 ± 0.02, and a zeta potential of 26.8 ± 2.5 mV. FTIR and TEM analyses, along with in vitro drug release and BBB permeability studies, confirmed their stability and efficacy. Behavioural tests, including the Elevated Plus Maze, Y-Maze, Object Recognition, and Locomotor Activity tests, demonstrated significant improvements in memory, motor coordination, and exploration time in the nanoparticle-treated groups. The group treated with ALN-βCD at a dose of 100 mg/kg/p.o. showed superior cognitive performance compared to the group receiving free andrographolides (AG). Biochemical assays indicated a significant reduction in acetylcholinesterase activity and lipid peroxidation, suggesting increased acetylcholine levels and reduced oxidative stress. Histopathological examination showed improved neuronal function without toxicity. The results showed significant improvements (p < 0.001) in memory and cognitive abilities in experimental animals, highlighting the potential of ALN-βCD nanoparticles as a non-invasive treatment for memory loss. These promising findings warrant further exploration through clinical trials.